Aplikacja systemu informacyjnego budżetowania w arkuszu kalkulacyjnym - Kes, Zdzisław (Application of System of Information Budgeting in Ms Excel, 2006)
The article describes system of information in budgeting. It performs characteristic of exit data of this system. It presents detailed characteristic of check report. The article includes description of exemplary function of information's system in budgeting. This system cooperates with MS Excel.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Finanse Bankowość Rachunkowość (4); 2006; nr 1119, s. 64-69